2008
DOI: 10.3357/asem.2205.2008
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine and Immune Responses to 16-Day Bed Rest with Realistic Launch and Landing G Profiles

Abstract: These data suggest a role for both catecholamines and glucocorticoids in mediating changes in leukocyte and lymphocyte subsets during simulated microgravity coupled with hypergravity. Our results were also strikingly similar to those from actual Shuttle missions and support our conclusion that we have developed a model of spaceflight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…11 Terrestrial space analog studies have suggested that altered leukocyte distribution in astronauts may result from stress and not microgravity conditions. 34 For ISS crews the WBC count was significantly elevated during missions at both the early and late time points, relative to the L-180 baseline data. No in-flight alterations were observed among the bulk lymphocyte, T and T-memory subsets, with the exception of an increased NK-cell concentration at the late in-flight timepoint.…”
Section: Discussionmentioning
confidence: 77%
“…11 Terrestrial space analog studies have suggested that altered leukocyte distribution in astronauts may result from stress and not microgravity conditions. 34 For ISS crews the WBC count was significantly elevated during missions at both the early and late time points, relative to the L-180 baseline data. No in-flight alterations were observed among the bulk lymphocyte, T and T-memory subsets, with the exception of an increased NK-cell concentration at the late in-flight timepoint.…”
Section: Discussionmentioning
confidence: 77%
“…For example, if repeated studies show that patients with neurological disease without rash that can be produced by VZV (e.g., vasculopathy, myelopathy or an ocular disorder) have VZV DNA or anti-VZV IgG antibody in CSF as well as VZV DNA in saliva, then the need for invasive lumbar punctures in such patients would be obviated. Finally, while passive drool is less expensive than synthetic swab, the latter must be used to obtain saliva from astronauts in space (Mehta et al, 2004) or in confined conditions encountered in Earth-based models that mimic stressful conditions experienced during spaceflight (Mehta et al, 2007; Stowe et al, 2008; Cohrs et al, 2009; Zwart et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed an increased or decreased plasma cortisol level depending on the duration of bed rest. 18,19 The levels of epinephrine and norepinephrine were increased in control and intervention groups in a study of Kanikowska and colleagues. 20 Yet another bed rest study showed an increase in noradrenalin, dopamine, adrenocorticotropic hormone, growth hormone, prolactin levels and decreased expression of interferon (IFN)-c during and after bed rest.…”
Section: Introductionmentioning
confidence: 99%